STRATEGI DIPLOMASI PUBLIK INDONESIA-MALAYSIA-THAILAND GROWTH TRIANGLE (IMT-GT) DALAM MENINGKATKAN SEKTOR PARIWISATA HALAL DI ASIA TENGGARA - Hesti rokhaniyah Rokhaniyah; Dinta Kharisma Almeira (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
This research aims at discussing the public diplomacy strategy of the Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) in promoting the halal tourism sector in Southeast Asia. This qualitative eserach used the document studies technique, which involved analyzing secondary data obtained from books, journals, websites, and reports. The data analysis techniques include data reduction, data presentation, and data interpretation. The research utilizes the concept of public diplomacy, which has three dimensions: news management, strategic communication, and relationship building, as well as international cooperation through Trilateral. The public diplomacy strategy implemented by IMT-GT for news management includes utilizing technology and mass media such as official websites, Instagram, YouTube, Twitter, Facebook, and creating a smartphone application to facilitate Muslim tourists in their travel and worship activities. The communication strategy is carried out by establishing the Halal Tourism Acceleration Team (TP3H), Working Groups on Halal Products (WGHAPASS), and the Halal Science Center of Chulalongkorn (HASCI). Relationship building is done through conducting training programs such as the Indonesia Muslim Travel Index (IMTI), the Malaysia International Halal Showcase (MIHAS), and the Thailand International Halal Expo (TIHEX). Through the Trilateral international cooperation between Indonesia, Malaysia, and Thailand, the halal industry in these three countries is growing and becoming more competitive at the global level.